إعادة هيكلة الجهاز المصرفي الجزائري ضمن متطلبات الحوكمة المالية الرشيدة. - غريسي, العربي; بلهاشمي, جهيزة (جامعة الوادي - University of Eloued, 2019)
نهدف من خلال هذه الدراسة الى معرفة مدى تاثير برامج اعادة الهيكلة المتبعة من قبل الحكومة الجزائرية من اجل اصلاح المنظومة المالية المصرفية في اطار التسيير الفعال للقطاع المصرفي على التطبيق الجيد لمعايير الحوكمة المالية حيث يعمل الجهاز المصرفي المتطور على تعبئة المدخرات من المقرضين الى المقترضين باقل تكلفة ممكنة وذلك من خلال تخفيض تكاليف ابرام الصفقات ،والتي تعتبر من اولويات نظرية حوكمة ،الى جانب العمل على تخفيض تكاليف الحصول على المعلومات حيث يتطلب عمل القطاع المصرفي ضرورة ارساء مبادئ الشفافية والمساءلة والمسؤولية الاجتماعية للمؤسسات المصرفية اتجاه الزبائن حيث يمثل تطبيق معايير الحوكمة المالية للمؤسسات المصرفية اتجاه المواطنين في اطار اعادة هيكلة الجهاز المصرفي من توجهات حكومات العديد من الدول ،وهذا ما نحاول توضيحه من خلال هذا البحث ،حيث تعتمد هذه الدراسة على تحليل وضعية مؤشرات الحوكمة المالية في الجزائر ومختلف برامج اعادة الهيكلة والتي توصلنا من خلالها لمجموعة من النتائج . Abstract: Through this study, we aim to determine the impact of the restructuring programs pursued by the Algerian Government in order to reform the banking financial system as part of the effective management of the banking sector in the good application of financial governance standards where the advanced banking system is working to mobilize the savings From lenders to borrowers at the lowest possible cost by reducing transaction costs, which are considered to be a corporate governance priority, while reducing the cost of access to information where the banking sector requires the need to establish the principles of transparency, accountability and social responsibility For banking institutions the direction of customers where the application of financial governance standards for banking institutions is the direction of citizens as part of the restructuring of the banking system from the direction of the governments of many countries, and this is what we are trying to clarify through this research, where this study depends on the analysis of the status of governance indicators Finance in Algeria and various restructuring programs through which we have reached a range of results.
Keywords: القطاع المالي ; الحوكمة المالية ; إعادة الهيكلة ; الشفافية والمساءلة